Allosteric mechanism in the distinctive coupling of G q and G s to the parathyroid hormone type 1 receptor - Xuan Zhang; Ji Young Lee; Jonathan Pacheco; Ieva Sutkeviciute; Anju Krishnan Anitha; Heng Liu; Stephanie Singh; Carlos Ventura; Sofya Savransky; Ashok Khatri; Cheng Zhang; Ivet Bahar; et al. (Proceedings of the National Academy of Sciences, 2025)
The mechanism determining the preferential stimulation of one heterotrimeric G protein signaling pathway over another by a ligand remains undetermined. By reporting the cryogenic electron microscopy (cryo-EM) structure of the parathyroid hormone (PTH) type 1 receptor (PTH1R) complexed with Gq and comparing its allosteric dynamics with that of PTH1R in complex with G s , we uncover a mechanism underlying such preferences. We show that an allosteric coupling between the ligand PTH and the C-terminal helix α5 of the Gα subunit controls the stability of the PTH1R complex with the specific G protein, G s or G q . Single-cell-level experiments further validate the G protein–selective effects of the PTH binding pose by demonstrating the differential, G protein–dependent residence times and affinity of this ligand at the PTH1R binding site. The findings deepen our understanding of the selective coupling of PTH1R to G s or G q and how it relates to the stability and kinetics of ligand binding. They explain the observed variability in the ligand-binding affinity of a GPCR when coupled to different G proteins.